PENERAPAN TEKNIK BERMAIN KARTU PINTAR UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR IPA - Surahmadi, Bambang (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
This study aims to determine the application of smart card-playing techniques to improve learning motivation and learning outcomes of science learners. The medium used is a smart card, a card which contains information contained in the subject matter learning objectives are packaged in the form of questions and answers. The research was conducted in SMP Negeri 1 Temanggung learners of class VIII G in 2nd semester Academic Year 2014/2015. The method used is a Class Action Research. Data collection methods used were questionnaires, pre-test and post-test. The research data in the form of learning outcomes IPA concept of test and motivation to learn is obtained from the questionnaire motivation. Statistical analysis showed in the first cycle an average yield is 56,67of pretest increased to an average is 70,58of posttes; the second cycle average is 62,24of pretest increased to an average is 80,86of posttest and third cycle average is 70,26 of pretest increased to an average is 84,24 of posttest While the motivation of learners increased by 86% from the prior-treated. Based on the results of the research, processing and data analysis and hypothesis testing measures taken in this study, we concluded that the application of smart card play technique can enhance learning motivation and learning outcomes of class VIIIG students of SMP Negeri 1 Temanggung.This study aims to determine the application of smart card-playing techniques to improve learning motivation and learning outcomes of science learners. The medium used is a smart card, a card which contains information contained in the subject matter learning objectives are packaged in the form of questions and answers. The research was conducted in SMP Negeri 1 Temanggung learners of class VIII G in 2nd semester Academic Year 2014/2015. The method used is a Class Action Research. Data collection methods used were questionnaires, pre-test and post-test. The research data in the form of learning outcomes IPA concept of test and motivation to learn is obtained from the questionnaire motivation. Statistical analysis showed in the first cycle an average yield is 56,67of pretest increased to an average is 70,58of posttes; the second cycle average is 62,24of pretest increased to an average is 80,86of posttest and third cycle average is 70,26 of pretest increased to an average is 84,24 of posttest While the motivation of learners increased by 86% from the prior-treated. Based on the results of the research, processing and data analysis and hypothesis testing measures taken in this study, we concluded that the application of smart card play technique can enhance learning motivation and learning outcomes of class VIIIG students of SMP Negeri 1 Temanggung.